Effects of stick design features on perceptions of characteristics of cigarettes. Issue 5 (6th March 2012) - Borland, Ron; Savvas, Steven
Abstract : Objective: To examine the extent (if any) that cigarette stick dimension, tipping paper design and other decorative design/branding have on Australian smokers' perceptions of those cigarettes. Methods: An internet survey of 160 young Australian adult ever-smokers who were shown computer images of three sets of cigarette sticks—five sticks of different lengths and diameters (set A), five sticks with different tipping paper design (set B) and four sticks of different decorative design (set C). Branding was a between-subjects randomised condition for set C. For each set, respondents ranked sticks on most and least attractive, highest and lowest quality and strongest and weakest taste. Results: Cigarette sticks were perceived as different on attractiveness, quality and strength of taste. Standard stick length/diameter was perceived as the most attractive and highest quality stick, with men more inclined to rate a slim stick as less attractive. A stick with a cork-patterned tipping paper and a gold band was seen as most attractive, of highest quality and strongest in taste compared to other tipping designs. Branded sticks were seen as more attractive, higher in quality and stronger tasting than non-branded designs, regardless of brand, although the effects were stronger for a prestige compared with a budget brand. Conclusions: Characteristics of the cigarette stick affect smokers' perceptions of the attributes of those cigarettes and thus are a potential means by which product differentiation can occur. A comprehensive policy to eliminate promotional aspects of cigarette design and packaging needs to include rules about stick design.